2009
DOI: 10.1007/s12016-009-8130-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Insights into Congenital Neutropenia

Abstract: Congenital neutropenia syndromes comprise a heterogeneous group of disorders leading to increased susceptibility to bacterial infections. Recent work has elucidated the molecular basis of several congenital neutropenia syndromes such as mutations in ELA2, HAX1, GF11, and WAS. In addition, a number of complex clinical syndromes associating congenital neutropenia have been recognized and elucidated on a genetic level, e.g. p14-deficiency or G6PC3-deficiency. The clinical and genetic findings of various neutropen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 78 publications
0
15
0
2
Order By: Relevance
“…In these cases the panel reckoned appropriate to proceed to further more targeted analyses (genomic DNA mutation study for Shwachman-Diamond, mitochondrial DNA analysis for Pearson's syndrome, erythrocyte ADA and mutation search for Blackfan-Diamond syndrome) [18][19][20][21] aiming to make a firm diagnosis of these diseases (Table VII) In the case of early, severe and recurrent infections associated to decreased Ig serum levels, increased CRP and positive markers LGL syndrome Associated to hypersplenism (AEanemia, AEthrombocytopenia) Associated to sequestration in infectious foci of infections, overall suggesting an immunodeficiency, peripheral blood immunophenotype, response to vaccines including polysaccharide antigens, lymphocyte proliferation to mytogens are indicated before referring the patient to an Immunodeficiency Reference Center where study of mutations of genes involved in neutropenia associated with immunodeficiency can be addressed [22][23][24][25][26][27][28][29][30][31][32][33][34] (Table VII) …”
Section: Diagnostic Itinerarymentioning
confidence: 99%
See 1 more Smart Citation
“…In these cases the panel reckoned appropriate to proceed to further more targeted analyses (genomic DNA mutation study for Shwachman-Diamond, mitochondrial DNA analysis for Pearson's syndrome, erythrocyte ADA and mutation search for Blackfan-Diamond syndrome) [18][19][20][21] aiming to make a firm diagnosis of these diseases (Table VII) In the case of early, severe and recurrent infections associated to decreased Ig serum levels, increased CRP and positive markers LGL syndrome Associated to hypersplenism (AEanemia, AEthrombocytopenia) Associated to sequestration in infectious foci of infections, overall suggesting an immunodeficiency, peripheral blood immunophenotype, response to vaccines including polysaccharide antigens, lymphocyte proliferation to mytogens are indicated before referring the patient to an Immunodeficiency Reference Center where study of mutations of genes involved in neutropenia associated with immunodeficiency can be addressed [22][23][24][25][26][27][28][29][30][31][32][33][34] (Table VII) …”
Section: Diagnostic Itinerarymentioning
confidence: 99%
“…In case these investigations fail to detect a genetic cause of SCN, the panel recommended to carefully re-evaluate history, clinical symptoms and specific laboratory tests. If also this re-evaluation process does not lead to identify a known genetic form of SCN then, based on the observation that forms of SCN exist without known genetic lesions [6,10,34,50,52,57], a diagnosis of SCN without known genetic lesion was reckoned as appropriate (EO, V, 8,1, B).…”
Section: (Eo 9 A)mentioning
confidence: 99%
“…Kostmann was thus the first to describe an inherited form of chronic neutropenia of childhood [6]. "Infantile agranulocytosis," as Rolf Kostmann named this hereditary syndrome, has been known for more than half a century, yet the underlying genetic mutations have remained unknown for many decades [17]. Recently, Klein et al demonstrated mutations in the most autosomal recessive severe congenital neutropenia (SCN) patients, including several originally studied by Kostmann.…”
Section: Anc Absolute Neutrophil Counts Ebpαmentioning
confidence: 99%
“…Otozomal dominant ağır konjenital nötropenilerin çoğundan ELA-2/ELANE (nötrofil elastaz) gen mutasyonları sorumlu iken, otozomal resesif formlardan HAX-1 (HS1-ilişkili protein X-1) mutasyonları sorumlu tutulmaktadır (3,4). Ağır konjenital nötropeniye neden olabilecek daha nadir diğer genler Glukoz-6-fosfataz katalitik alt birim 3 (G6PC3), WiskottAldrich sendromu ve bağımsız büyüme faktörü-1'dir (GFI-1) (3)(4)(5).…”
Section: Introductionunclassified
“…Ağır konjenital nötropeniye neden olabilecek daha nadir diğer genler Glukoz-6-fosfataz katalitik alt birim 3 (G6PC3), WiskottAldrich sendromu ve bağımsız büyüme faktörü-1'dir (GFI-1) (3)(4)(5). Koloni stimüle edici faktörlerinin (G-CSF) kullanımından önce bu hastalık ilk 1 yıl içinde sıklıkla fatal seyretmekte iken G-CSF tedavisi ile hastaların ortalama yaşam süreleri belirgin olarak artmıştır.…”
Section: Introductionunclassified